Osobine ličnosti učenika, strategije samoregulacije učenja i suočavanja sa školskim neuspjehom, dob i rod kao prediktori objektivnoga i subjektivnoga školskog uspjeha - Nikčević-Milković, Anela; Tatalović Vorkapić, Sanja (2020)
Cijeli niz istraživanja potvrđuje povezanost između osobina ličnosti, samoregulacije učenja i školskoga postignuća, iako te povezanosti nisu jednostavne. Osobine ličnosti važni su prediktori objašnjenja samoregulacije učenja, a jedno i drugo važni su prediktori objašnjenja objektivnoga i subjektivnoga školskog uspjeha, odnosno zadovoljstva školom. Osnovni je cilj ovoga istraživanja bio ispitati u kojoj mjeri demografske karakteristike učenika (dob i rod), osobine ličnosti, (meta)kognitivne strategije učenja, strategije suočavanja sa školskim neuspjehom i strategije traženja socijalne podrške (kao prediktori) objašnjavaju objektivni i subjektivni školski uspjeh (kao kriterije). U istraživanju je sudjelovalo 457 učenika 6. i 8. razreda osnovne škole i 2. razreda srednje škole iz četiriju osnovnih i triju srednjih škola u Republici Hrvatskoj. Rezultati pokazuju da se s povećanjem dobi smanjuje objektivni školski uspjeh. Učenice imaju veći objektivni školski uspjeh, kao i savjesniji učenici te oni učenici koji manje koriste maladaptivne strategije površinskoga kognitivnog procesiranja informacija (što je i najznačajniji negativni prediktor objektivnoga školskog uspjeha). Navedeni set prediktora uspješno je objasnio 29 % objektivnoga školskog uspjeha kao kriterija. S povećanjem dobi učenika smanjuje se i subjektivni školski uspjeh. Učenici koji su viši na osobini Ugodnosti, koji manje koriste maladaptivne strategije zaštite emocija udaljavanjem prilikom suočavanja sa školskim neuspjehom, a više rabe adaptivne strategije traženja emocionalne i instrumentalne podrške od prijatelja, imaju veći subjektivni školski uspjeh. Navedeni set prediktora uspješno je objasnio 18 % subjektivnoga školskog uspjeha kao kriterija.
Series of studies have confirmed the significant correlation between personality traits, selfregulation of learning and academic achievement, although these relations are not simple. Personality traits are important predictors of self-regulation of learning, and both are significant predictors of the explanation of objective and subjective school achievement (school satisfaction). The main objective of this research was to examine the extent to which demographic characteristics of students (age and gender), personality traits, the (meta)cognitive strategies of self-regulation of learning, the coping strategies with school failure and the strategy of seeking social support (as predictors) explain objective and subjective school achievement (as criteria). Total of 457 students from 6th and 8th grade of elementary school and 2nd grade of high school from four elementary and three secondary schools in the Republic of Croatia participated in the study. The results show that objective school achievement decreases as students’ age increases. Female students have higher objective school achievement, as well as more conscientious students and those students who less rely on maladaptive strategies of surface cognitive information processing (which is also the most significant negative predictor of objective school success). The above set of predictors successfully explained 29 % of objective school achievement as a criterion. Subjective school achievement also decreases with increased age. Students who are higher on the Agreableness, who less rely on maladaptive strategies of Protection of emotions by moving away when facing school failure, and use more adaptive strategies Ask for emotional and instrumental support from friends, have greater subjective school success. The above set of predictors successfully explained 18 % of subjective school performance as a criterion.
Bibliografija: str. 500-506.
Sažetak ; Summary.
Keywords: Osobine ličnosti -- Učenici -- Samoregulacija učenja -- Dob -- Rod -- Školsko postignuće